2010
DOI: 10.3109/15622975.2010.526146
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of the pro-oxidant xanthine oxidase (XO) in the thalamus and occipital cortex of patients with schizophrenia

Abstract: Nevertheless, our results might suggest a downregulation of cellular defence mechanisms in schizophrenia in several brain regions, which could account for neuronal alterations which have been described before. This demonstrates that more research is needed to fully understand the role of the complex enzyme XO in the pathophysiology of schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 72 publications
(97 reference statements)
0
17
0
7
Order By: Relevance
“…Reduced activity of xanthine oxidase in the thalamus and occipital cortex of patients with chronic schizophrenia was observed. Studies show that elevated levels of xanthine oxidase also occur in the blood of schizophrenic patients [184].…”
Section: Uracil Xanthine Oxaninementioning
confidence: 99%
“…Reduced activity of xanthine oxidase in the thalamus and occipital cortex of patients with chronic schizophrenia was observed. Studies show that elevated levels of xanthine oxidase also occur in the blood of schizophrenic patients [184].…”
Section: Uracil Xanthine Oxaninementioning
confidence: 99%
“…Xanthine oxidase (XO) is an enzyme of special interest in this context, since it acts as a prooxidant, but its main product uric acid is a powerful antioxidant. By examining the activity of XO in the occipital cortex and thalamus of patients with psychosis, the authors found a decreased activity of XO suggesting a downregulation of cellular defence mechanisms in schizophrenia [176]. …”
Section: Peroxisome Proliferator-activated Receptor-gamma Agonistsmentioning
confidence: 99%
“… 71 Pro-oxidant xanthine oxidase (XO), which is found to play an integral role in purine/adenosine metabolism has decreased activity of XO in the occipital cortex and thalamus of patients with psychosis. 72 …”
Section: Metabolic Changes Involving the Occipital Lobe In Schizophrementioning
confidence: 99%